The Role of Accounting And Auditing Organization For Islamic Financial Institutions (AAOIFI) in Sharia Statement Of Fiancial Accounting Standards (PSAK) - Seniwati Sembiring; Ahmad Muhajir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research is intended to provide an understanding of Islamic financial accounting standards. In carrying out its sharia principles, sharia banks must also uphold the values of justice, trust, partnership, transparency and mutual benefit for both the bank and for customers which are the pillars in carrying out muamalah activities . With the rapid growth rate of Islamic Financial Institutions in the world, an appropriate standard is needed in presenting financial reports to overcome differences in the preparation of each country. The role of AAOIFI in this regard has greatly contributed in terms of the formulation of standards, although in practice there are many obstacles to its application, moreover the standard that is widely used by countries is IFRS and it is not easy for countries to adopt AAOIFI standards in a short time . Most of the standards used by Islamic banking follow the AAOIFI standards adopted in the Sharia PSAK but in relation to IFRS standards are also applied as long as they do not conflict with sharia principles and values.